A Study on Foreign Direct Investment and Its Impact on Retailing Sector: Examining the Effects of FDI on India's Retailing Sector (Journal of Advances and Scholarly Researches in Allied Education, 2014)
India has growthprospect for retail industry with a huge number of consumers and other favorablefactors. But India’s retail market remains largely off-limits to largeinternational retailers like Wal-Mart, Tesco and Carrefour. Opposition toliberalizing FDI in this sector raises concerns about employment losses, unfaircompetition resulting in large-scale exit of incumbent domestic retailers andinfant industry arguments to protect the organized domestic retail sector thatis at a nascent stage. In 2012 the Indian Government approved proposal of 100percent FDI in retailing in India subject to certain conditions. Though thisproposal  is being hailed by global  retail giants, which  until  now have  been  involved in  only wholesale  cash and  carry distribution  in India and have been  longing forentry  into  the Indian retail market for years. The proposal has received vehement opposition from a spectrum ofpolitical parties in India, many of them urging for a reversal of the proposal.As a  result,  the Indian government has stalled the  implementation of  this proposal which has  temporarily washed off  the wishes of the  global retail  players  awaiting a  bite  of the  Indian  retail market. This paper attempts to studythe present status of FDI in retailing sector in India and the impacts of FDIon various concerned segments.